Potensi Penyebaran Covid-19 di Objek Wisata Indoor Sumatera Barat Berdasarkan Kualitas Fisik Udara Studi Kasus: Lubang Japang dan Istano Basa Pagaruyung - Resti Ayu Lestari; Rinda Andhita Regia; Hafifatul Auliya Rahmy; Vezy Hidayatifa Thayyibah; Nadya Fadhillah Febrinaldi (Fakultas Teknik, 2021)
The Covid-19 pandemic is affecting indoor tourism in West Sumatra. The spread of a virus through could be influenced by indoor air quality. This study aims to analyze the potensial spread of Covid-19 in the indoor tourism in West Sumatra based on the physical indoor air quality, including PM2.5 concentration, temperature, humidity, and light intensity. The research objects were Lubang Japang Bukittinggi and Istano Basa Pagaruyung. The research was conducted by using sampling and interview methods. The data obtained were compared to Permenkes No. 1077/Menkes/Per/V/2011 and the suitable environmental conditions for the virus. The results showed that the temperature values in tourist objects were below the standards used. The temperature value in the research objects ranged from 20oC to 30oC. The humidity, light intensity, and PM2.5 concentration values were outside the ranges stipulated by regulations. Lubang Japang humidity was: 75.97 - 94.76 Rh; Istano Basa Pagaruyung: 65.83 - 67.16 Rh. Lubang Japang light intensity was: 0.4 - 4.0 Lux; Istano Basa Pagaruyung: 28 - 38 Lux. The concentration of PM2.5 at Lubang Japang: 187.45 µg / Nm3; Istano Basa Pagaruyung: 77.29 µg / Nm3. Based on this research, the humidity and the PM2.5 concentration of the research objects have the potential to spread the Covid-19.